Experimental assessment of film cooling from cylindrical holes subject to particulate deposition - Yang, Xing; Hao, Zihan; Feng, Zhenping (Experimental thermal and fluid science, 2024)
•Coupling effects of particulate deposition and film cooling were experimentally examined.•Links between deposition thickness and film cooling effectiveness were quantitatively assessed.•Film holes with a compound angle is more sensitivity to deposition.•Increasing coolant injection rates is helpful to mitigate deposition effects. Particulate deposition has become a significant challenge of developing more efficient film cooling configurations for hot turbine components. To assess the influence of particulate deposition and to better understand the coupling effects of deposition evolution and film cooling, experimental simulations were conducted by injecting low-melting-point wax particles into a low-temperature wind tunnel facility, in which the particle transport and sticking behaviors were properly modeled by matching critical non-dimensional parameters in engine conditions. The sensitivity of film cooling to deposition was assessed on flat plates with a row of simple-angled film holes and compound-angled film holes, respectively. Local deposition patterns were obtained using an optical profile scanner and an infrared thermography technique was implemented to quantify the development of film cooling with the evolution of deposition. Further, flow fields downstream of the holes and coolant trajectories were visualized by means of a five-hole probe and a schlieren photography technique, offering the flow physics backing the observation of film cooling. Inspection of deposition over the flat plates revealed that film cooling was helpful to inhibit deposition, which leads to sparse deposition near the hole exit and dense deposition elsewhere. Film injection from the compound-angled hole was found to be more sensitive to deposition, resulting in decreased cooling effectiveness regardless of coolant blowing conditions. In contrast, deposition reduced film cooling from the simple-angled hole at lower injection rates and then improved film cooling at higher injection rates. Globally, the compound-angled hole exhibited a maximum reduction of 20 % in cooling effectiveness, while that for the simple-angle hole was 8.5 % at an injection ratio of 0.5; and at a high injection ratio of 2.0, an improvement of 13.6 % was obtained, on the contrary.